DETERMINAN KARAKTERISTIK PERUSAHAAN TERHADAP ENVIRONMENTAL DISCLOSURE (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2012-2016) - Puji Nurhayati; Sari Kurniati (Universitas PGRI Madiun, 2019)
This study aims to examine the influence of company characteristics which include profitability, leverage and company size on environmental disclosure. The data used in this study is secondary data with the number of 270 manufacturing companies listed on the Indonesia Stock Exchange in 2012-2016. Data testing uses multiple regression through SPSS software. The test results prove that the profitability and size of the company affect environmental disclosure while leverage does not affect environmental disclosure.